Fermi Velocity Reduction of Dirac Fermions around the Brillouin Zone Center in In2Se3–Bilayer Graphene Heterostructures. Issue 17 (19th March 2021) - Wang, Zhenyu; Hao, Zhanyang; Yu, Yayun; Wang, Yuan; Kumar, Shiv; Xie, Xiangnan; Tong, Mingyu; Deng, Ke; Hao, Yu‐Jie; Ma, Xiao‐Ming; Zhang, Ke; Liu, Cai; et al.
Abstract: Emergent phenomena such as unconventional superconductivity, Mott‐like insulators, and the peculiar quantum Hall effect in graphene‐based heterostructures are proposed to stem from the superlattice‐induced renormalization of (moiré) Dirac fermions at the graphene Brillouin zone corners. Understanding the corresponding band structure commonly demands photoemission spectroscopy with both sub‐meV resolution and large‐momentum coverage, beyond the capability of the current state‐of‐the‐art. Here the realization of moiré Dirac cones around the Brillouin zone center in monolayer In2 Se3 /bilayer graphene heterostructure is reported. The renormalization is evidenced by reduced Fermi velocity (≈ 23%) of the moiré Dirac cones and the reshaped Dirac point at the Γ point where they intersect. While there have been many theoretical predictions and much indirect experimental evidence, the findings here are the first direct observation of Fermi velocity reduction of the moiré Dirac cones. These features suggest strong In2 Se3 /graphene interlayer coupling, which is comparable with that in twisted bilayer graphene. The strategy expands the choice of materials in the heterostructure design and stimulates subsequent broad investigations of emergent physics at the sub‐meV energy scale. Abstract : A practical strategy to construct moiré Dirac cones around the Brillouin zone center is realized by folding graphene Dirac cones in monolayer In2 Se3 /bilayer graphene heterostructures. The Fermi velocity of the moiré Dirac cones is reduced by ≈23%, and the reshaped Dirac point at the Γ point is elongated. Both features further confirm the moiré Dirac fermion renormalization and interactions.